2013
DOI: 10.1016/j.joep.2013.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wages on public officials’ corruptibility: A laboratory investigation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 59 publications
0
38
0
3
Order By: Relevance
“…Rauch and Evans (2000) [13] and Treisman (2000) [15] find no correlation while the other two find weak evidence in favour of the hypothesis that raising wages of public officials leads to reduced corruption. Van Veldhuizen (2013) [22] undertakes an experimental study and shows that higher wages lead to significantly lower corruption on the part of officials. However, the result does depend on the frequency of monitoring of the official's action.…”
Section: Introductionmentioning
confidence: 99%
“…Rauch and Evans (2000) [13] and Treisman (2000) [15] find no correlation while the other two find weak evidence in favour of the hypothesis that raising wages of public officials leads to reduced corruption. Van Veldhuizen (2013) [22] undertakes an experimental study and shows that higher wages lead to significantly lower corruption on the part of officials. However, the result does depend on the frequency of monitoring of the official's action.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, the government is the principal and the public official is the agent (Becker and Stigler, 1974;Van Rijckeghem and Weder, 2001). Experimental studies have shown that the agents' willingness to engage in corruption is affected by the level of wages (Abbink, 2005;Armantier and Boly, 2011;van Veldhuizen, 2013), the monitoring capacity (Azfar and Nelson, 2007;Olken, 2007;Barr et al, 2009;Serra, 2012), the risk of penalty (Abbink et al, 2002), staff rotation (Abbink, 2004), asymmetric liability (Abbink et al, 2014), or information (Berninghaus et al, 2013;di Falco et al, 2016). Generally, it has been found that officials with higher wages, subject to rigorous monitoring and severe punishment when corruption is detected are less corrupt (see Abbink and Serra, 2012, for a review).…”
Section: Related Literaturementioning
confidence: 99%
“…Schulze y Frank (2003), en su experimento sin riesgo, observan que el salario no tiene efecto, pero al introducir el riesgo de ser descubierto, sí hay un costo de oportunidad y un salario fijo disminuye los niveles de sobornos. Veldhuizen (2013) confirma este resultado. Aumentar el salario reduce de manera significativa la corrupción, pero sus resultados sugieren que este efecto positivo depende de la existencia de controles.…”
Section: Salariounclassified